2018
DOI: 10.1039/c8ra02449a
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of mass-selected bimetallic Pt–Ti nanoalloys to oxygen explored using scanning transmission electron microscopy and density functional theory

Abstract: The response of nanoparticles to exposure to ambient conditions and especially oxidation is fundamental to the application of nanotechnology. Bimetallic platinum-titanium nanoparticles of selected mass, 30 kDa and 90 kDa, were produced using a magnetron sputtering gas condensation cluster source and deposited onto amorphous carbon TEM grids. The nanoparticles were analysed with a C s -corrected Scanning Transmission Electron Microscope (STEM) in High Angle Annular Dark Field (HAADF) mode. It was observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Composite nanostructures of noble metal or bimetals of (Au, Ag, Pt or Pd) and titania or zinc oxide are of great interest because of the plasmon-induced enhancement of their photovoltaic efficiency and photocatalytic activity [8][9][10], for biomedicine and sensing applications [11,12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Composite nanostructures of noble metal or bimetals of (Au, Ag, Pt or Pd) and titania or zinc oxide are of great interest because of the plasmon-induced enhancement of their photovoltaic efficiency and photocatalytic activity [8][9][10], for biomedicine and sensing applications [11,12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, for bimetallic TiPt NPs used in fuel cells it has been found that their oxidation can facilitate the formation of multiple core and shell NPs. 14 Bimetallic PdRu NPs have been reported to provide more efficient catalytic reactionssuch as CO x conversion, NO x conversion, and hydrogenation reactionsthan their parent metallic NPs. [15][16][17][18] HAADF-STEM images claried the Pd and Ru atoms are homogeneously distributed in the synthesized NPs at room temperature.…”
Section: Introductionmentioning
confidence: 99%